Etiology, diagnosis and treatment of Ludwig’s Angina - Review of the literature (Research, Society and Development, 2022)
Ludwig's angina is a severe infectious cellulitis that tends to have a rapid progression on the floor of the mouth, involving the submandibular, submaxillary, and sublingual spaces of the face, usually in association with non-vital dental organs although any other oropharyngeal infection has the capacity to trigger Ludwig's angina. It can become fatal if not recognized early and may cause complications such as sepsis and asphyxia by expanding soft tissue swelling of the neck, leading to airway compromise. Immunosuppressed patients with systemic involvement are more susceptible to Ludwig's Angina. After confirmation of the diagnosis, the treatment is based on drainage, removal of the cause, airway maintenance, antibiotic therapy, and parenteral hydration of the patient. Objective: This study aims to report through a literature review the relevance of signs and symptoms in the outcome of Ludwig's Angina, its main causes, affected groups, types of treatment, and cervicofacial and systemic complications, seeking to generate a better understanding about the management of patients with Ludwig's Angina, offering the reader information about the etiology, diagnosis and treatment, as well as the prognosis regarding the established treatment. Early recognition and rapid intervention are essential for the containment of this serious condition.